The impact of the SARS-COV-2 pandemic on the quality of breast cancer care in EUSOMA-certified breast centres. (December 2022) - van Dam, Peter; Tomatis, Mariano; Ponti, Antonio; Marotti, Lorenza; Aristei, Cynthia; Biganzoli, Laura; Cardoso, Maria J; Cheung, Kwok L; Curigliano, Giuseppe; De Vries, Jakob; Santini, Donatella; Sardanelli, Francesco; et al.
Abstract: Aims: We analysed the impact of the SARS-CoV-2 pandemic (COVID-19) on the quality of breast cancer care in certified EUSOMA (European Society of Breast Cancer Specialists) breast centres. Materials and methods: The results of the EUSOMA quality indicators were compared, based on pseudonymised individual records, for the periods 1 March 2020 till 30 June 2020 (first COVID-19 peak in most countries in Europe) and 1 March 2019 till 30 June 2019. In addition, a questionnaire was sent to the participating Centres for investigating the impact of the COVID-19 pandemic on the organisation and the quality of breast cancer care. Results: Forty-five centres provided data and 31 (67%) responded to the questionnaire. The total number of new cases dropped by 19% and there was a small significant higher tumour (p = 0.003) and lymph node (p = 0.011) stage at presentation. Comparing quality indicators (12, 736 patients) by multivariable analysis showed mostly non-significant differences. Surgery could be performed in a COVID-free zone in 94% of the centres, COVID testing was performed before surgery in 96% of the centres, and surgical case load was reduced in 55% of the centres. Modifications of the indications for neoadjuvant endocrine therapy, chemotherapy, and targeted therapy were necessary in 23%, 23%, and 10% of the centres; changes in indications for adjuvant endocrine, chemo-, targeted, immune, and radiotherapy in 3%, 19%, 3%, 6%, and 10%, respectively. Conclusion: Quality of breast cancer care was well maintained in EUSOMA breast centres during the first wave of the COVID-19 pandemic. A small but significantly higher tumour and lymph node stage at presentation was observed. Highlights: Patients registered in eusomaDB dropped by 19% in the first wave of COVID-19. We found higher tumour (p = 0.003) and lymph node (p = 0.011) stage at presentation. Changes in locoregional and adjuvant treatment were seen in patients aged >70. QIs multivariate analysis in two time periods shows no significant differences. Quality was maintained in EUSOMA breast centres during the first wave of COVID-19.